A research on Early Motivation of First Years Students of Tadulako University in Learning English - Ananda Mumtahana; Afrillia Anggreni; Mochtar Marhum; Nadrun, Nadrun (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The research deals with the intrinsic and extrinsic motivation of First year students in learning English. In addition this research also identifies the students’ effort to enhance their motivation. Qualitative design was implemented to find out the the first year students’ motivation in learning English, specifically to their intrinsic and extrinsic motivation. The participants consisted of 71 students of English Education Deapartement of Tadulako University in Batch 2023-2024. The questionnaire was the instrument used in collecting data. The questionnaire consisted of 17 items items, 6 items about intrinsic motivation, 6 items about extrinsic motivation and 5 items related to students’ efforts to enhance their motivation in learning English. The results show that in intrinsic, Knowledge development is prior motives of the students in learning english and in extrinsic is environtment- oriented. In addition, for efforts of the students in enhanching their motivation are improving english’ vocabulary, writing practice and reading english articles. This research implies that becoming a teacher and parents’ supporting are not primary motives of the students in learning English.